Analisis Ketahanan Pangan Pasca Pandemi Kota dan Kabupaten di Provinsi Termiskin Kedua Pulau Sumatera - Wibowo, Hariz Eko; Novanda, Ridha Rizki; Ifebri, Rihan; Fauzi, Ariffatchur (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Food security is one of the maqashid of sharia (sharia goals), namely protecting the soul (hifz al-nafs). Food security is important in maintaining the life and sustainability of humanity. Because affordability is a component of food security, there is a close relationship between food security and poverty. Bengkulu Province is the second largest province with a percentage of people living in poverty on the island of Sumatra. However, the percentage of people in Bengkulu Province who live in poverty tends to be unaffected by the pandemic and is even showing signs of decreasing. The results of other studies on the impact of the pandemic on poverty, income and food security contradict this. Therefore, it is necessary to conduct research regarding changes in food security after the pandemic in cities and districts in Bengkulu Province. The results of this descriptive analysis show that almost all city and district food security indices have not experienced significant changes after the Covid-19 pandemic in Bengkulu Province. Only Mukomuko Regency and Bengkulu City experienced significant changes, namely changing from the